The Effect of Competence and Organizational Culture on Employee Performance with Career Development as an Intervening Variable - Rumbekwan, Leunard Herman Fransiscus; Zakaria, Zakaria; Mulyanti, Rita Yuni (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study examines the impact of competence and organizational culture on employee performance, both directly and through career development, at the Department of Fisheries in Merauke Regency. Employing a quantitative causal approach, data were collected from 107 employees via a survey and analyzed using Structural Equation Modeling (SEM) with AMOS 24.00. Findings reveal that competence indirectly affects performance through career development, while organizational culture influences performance directly and indirectly. Career development mediates the effects of competence and culture on performance. This study suggests enhancing career development to improve employee performance, considering competence and organizational culture.